Environmental silicate nano-biocomposites - Pollet, Eric; Averous, Luc (Green energy and technology,, 2012)
Environmental Silicate Nano-Biocomposites focuses on nano-biocomposites, which are obtained by the association of silicates such as bioclays with biopolymers. By highlighting recent developments and findings, green and biodegradable nano-composites from both renewable and biodegradable polymers are explored. This includes coverage of potential markets such as packaging, agricultures, leisure and the fast food industry. The knowledge and experience of more than twenty international experts in diverse fields, from chemical and biochemical engineering to applications, is brought together in four different sections covering: Biodegradable polymers and Silicates, Clay/Polyesters Nano-biocomposites, Clay/Agropolymers Nano-biocomposites, and Applications and biodegradation of Nano-biocomposites. By exploring the relationships between the biopolymer structures, the processes, and the final properties Environmental Silicate Nano-Biocomposites explains how to design nano-materials to develop new, valuable, environmentally friendly properties and uses. The combination of fundamental and applied science makes this an ideal reference for a range of readers from students and lecturers to material and polymer scientists and even industrial engineers who are interested in bringing new environmental nano-materials to the current market.